Coastal structures and breakwaters proceedings of the conference organized by the Institution of Civil Engineers, and held in London on 6-8 November 1991. (Thomas Telford, 1992)
This volume presents authoritative research on new experience and research on coastal structures and breakwaters, particularly that which has led to advance in design procedures.